(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2010)
facing economic units operating in the environment sector of the Iraqi industrial many pressures in its seeking to measure and evaluate its performance because of variables, today’s corporate environment, as the case which makes looking for a methodology can be adopted to evaluate its performance with a more holistic, rather than being limited to traditional measures that are no longer enough to keep pace with rapid changes in today’s corporate environment, which requires that measures of performance are derived from the strategy of unity and commensurate with the specificity of the environment in Iraq. Try searching discussion Ttormwhrat and performance measurement systems to suit the business strategies and directions of change which, leading up to give background on what the technical card performance measurement balanced and developments associated with the first generation to third generation and how to prepare, then access to the main part in the research and associated Bagtra mechanism for implementing the indicators and dimensions contained in the card in the performance evaluation of the strategic units of the Iraqi industrial output and thus the use of the card inputs contribute to strengthening the competitive position of the units and keep them in light of contemporary business environment variables.